Success rate of acceleromyographic neuromuscular monitoring based on the depth of anesthesia at the time of sugammadex antagonism: a randomized controlled trial - Hwang-Ju You; Seok-Jin Lee; Ji-Yoon Jung; Sung-Ae Cho; Woojin Kwon; Jin-Bum Kim; Tae-Yun Sung (Journal of International Medical Research, 2024)
Objective We aimed to compare the success of non-normalized acceleromyographic neuromuscular monitoring and recovery profiles based on the depth of anesthesia at the time of sugammadex administration. Methods Patients undergoing general anesthesia were prospectively and randomly allocated to two groups. In the BIS60 group, sugammadex was administered when there was a bispectral index (BIS) <60 and anesthesia was maintained until a train-of-four ratio ≥1.0 was obtained, whereas in the BIS70 group, anesthesia was stopped at the completion of surgery, sugammadex was administered when the BIS was >70, and the recovery of neuromuscular function was monitored. The recovery profile and the incidence of emergence agitation of the two groups were compared. Results The success rate of neuromuscular monitoring was significantly higher for the BIS60 group than for the BIS70 group (100% vs . 37.5%, respectively). The time taken for recovery for the two groups was comparable. The incidence of emergence agitation was significantly lower in the BIS60 group than in the BIS70 group (23.3% vs . 56.3%, respectively). Conclusion After the administration of sugammadex, the maintenance of anesthesia until the full recovery of neuromuscular function increases the success rate of neuromuscular monitoring without delaying recovery and reduces the risk of emergence agitation. Clinical trial registration: CRIS registration number KCT0007899 ( https://cris.nih.go.kr/ )